GREEN ECONOMY AND LOW CARBON DEVELOPMENT DRIVE NATIONAL ECONOMIC GROWTH AND IMPROVE SOCIAL WELFARE - Putri, Rumanintya Lisaria; Werastuti, Desak Nyoman Sri; Saptana; Wahyono, Eko; Hastuty, Ernany Dwi (Laboratorium Riset Ekonomi, 2023)
All countries affected by COVID-19 are facing difficult problems in overcoming the outbreak and the socio-economic impacts it has caused. The aim of this research was to determine the effect of a green economy and low carbon development on green growth and multilateral issues. This research is a descriptive research that uses a literature study type or approach. The results of the study reveal that the application of a green economy is able to encourage national economic growth and problems in the multilateral field, as well as improve social welfare. In order for a green economy to be realized for the country, various parties must support policy makers so that a sustainable green economy can be created. The green economy also contributes to maintaining environmental sustainability and forming ecosystems that can be enjoyed by present and future generations.